2019
DOI: 10.1111/petr.13541
|View full text |Cite
|
Sign up to set email alerts
|

Late allograft fibrosis in pediatric liver transplant recipients: Assessed by histology and transient elastography

Abstract: Late allograft fibrosis in LT recipients can cause graft dysfunction and may result in re‐transplantation. TE is a non‐invasive tool for the assessment of liver fibrosis. We aimed to evaluate the prevalence of allograft fibrosis in pediatric LT recipients, identify factors associated with allograft fibrosis, and determine the diagnostic value of TE, compared to histology. All children who underwent LT for ≥3 years were included. TE was performed for LSM in all patients. LSM of ≥7.5 kPa was considered as abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…Although clinical application of these laboratory parameters is limited, as fibrosis of the graft can occur with completely normal laboratory indicators, it is possible that these routinely obtained values may suggest those patients in need of further evaluation with LSM. Time from transplant, history of ACR, history of rejection, or type of immunosuppressant medication had no correlations with LSM, which is different from previously published data 20 . While these factors may affect liver fibrosis and LSM, we likely did not find a statistical significance due to our small sample size.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although clinical application of these laboratory parameters is limited, as fibrosis of the graft can occur with completely normal laboratory indicators, it is possible that these routinely obtained values may suggest those patients in need of further evaluation with LSM. Time from transplant, history of ACR, history of rejection, or type of immunosuppressant medication had no correlations with LSM, which is different from previously published data 20 . While these factors may affect liver fibrosis and LSM, we likely did not find a statistical significance due to our small sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…These results support and add to previously published data also showing a correlation between liver stiffness and hepatic fibrosis 13,14 . Our data conflict with a recent study which showed only a 66.7% accuracy of LSM in predicting fibrosis 20 . We were also able to provide a cutoff value of 7.25 kPa that is helpful in predicting significant graft fibrosis.…”
Section: Discussionsupporting
confidence: 57%
“…TE is an ultrasound-based method that measures liver stiffness, which has been shown to correlate with the histological degree of been reported only in a few small studies (4). 15,[19][20][21] The first study published in 2013 showed that TE performed In our cohort, neither APRI nor FIB-4 appeared to be useful in discriminating between patients with F0/F1 and F2-F4 fibrosis.…”
Section: Discussionmentioning
confidence: 57%
“…Its use in children who have received LT has been reported in only a few small studies. 15,[19][20][21] The aim of this study was to evaluate the ability of TE to predict clinically significant, histologically assessed liver graft fibrosis (METAVIR F2-F4) in a large cohort of pediatric and young adult LT recipients at a single transplant center. Secondary aims were (a) to compare the predictive ability of TE to that of the APRI and the FIB-4, and (b) to investigate whether or not graft type had any effect on the performance of LSMs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation